The role of decimeter-scale surface roughness in passive remote sensing of sea ice in L-band - Miernecki, Maciej (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
In this study we investigate the influence of large scale surface deformation on sea ice brightness temperature (TB ) at 1.4 GHz (L-band). Additionally we investigate the possibility of detecting the sea ice deformation with L-band radiometry. The European Space Agency’s SM OS mission is the first space-borne radiometer carrying out multi-angular measurements at the frequency of 1.4 GHz. The L-band TB is sensitive to sea ice thickness, and therefore is used for sea ice thickness retrieval over thin sea ice. Snow cover is another factor that influences the L-band TB over sea ice, this property can be used to infer the snow depth over thick ice. However, the effect of the surface roughness on sea ice TB is not well characterized. In the following study we address this knowledge gap by using a combination of experimental data from field campaign and a sea ice emission model. We use the airborne laser scanner (ALS) to characterize sea ice surface roughness off-coast of Svalbard during SM OSice2014 campaign. Then, we use the geometrical optics and surface slopes probability density functions to simulate emissions from a random faceted surface. Emissions from individual facets are calculated with MIcrowave L-band LAyered Sea ice emission model (M ILLAS). Finally, we compare several simulations with different roughness setups with EM IRAD2 radiometer data from SM OSice2014 campaign. In dieser Studie untersuchen wir den Einfluss der großflächigen Oberflächenverformung auf die Meereis-Helligkeitstemperatur (TB ) bei 1.4 GHz (L-Band). Zusätzlich untersuchen wir die Möglichkeit, die Meereisverformung mit Hilfe von L-Band-Radiometrie zu detektieren. Die SM OS Mission der Europäischen Weltraumorganisation ist das erste Weltraumradiometer, das Messungen mit einer Frequenz von 1.4 GHz unter verschiedenen Einfallswinkeln durchführt. Die L-Band TB ist empfindlich gegenüber Meereisdicke und wird daher für die Meereisdicken-Berechnung über dünnem Meereis verwendet. Schneebedeckung ist ein weiterer Faktor, der die ...